In Vitro Susceptibility of Multidrug Resistant Skin and Wound Pathogens Against Low Temperature Atmospheric Pressure Plasma Jet (APPJ) and Dielectric Barrier Discharge Plasma (DBD). Issue 2 (9th December 2013) - Daeschlein, Georg; Napp, Matthias; von Podewils, Sebastian; Lutze, Stine; Emmert, Steffen; Lange, Anja; Klare, Ingo; Haase, Hermann; Gümbel, Denis; von Woedtke, Thomas; Jünger, Michael
<x xml:space="preserve">Abstract</x> Plasma medicine has become an emerging field in medical sciences since cold plasma has demonstrated important antimicrobial properties. As microbial plasma susceptibility data yet are not available, the susceptibility of 194 wound isolates exhibiting multiple antibiotic resistance was tested in vitro to CP and correlated with inhibition zones. Inhibition zones increased in parallel with the number of antibiotic classes to which the tested strain exhibit resistance. CP exhibited strong antimicrobial efficacy against most important clinical skin and wound pathogens in vitro irrespective of multidrug resistance.<inline-graphic xlink:href="ark:/27927/pgg4sq5xnnc" content-type="ppap201300070-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />